2018
DOI: 10.9734/jammr/2018/41050
|View full text |Cite
|
Sign up to set email alerts
|

Acute Childhood Poisoning in Azare North Eastern Nigeria

Abstract: Aim: To describe the clinical profile of acute poisoning amongst children admitted into the Federal Medical Centre Azare, Nigeria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…[ 6 ] Economic hardship leads to overcrowded living with limited storage space for toxic substances away from the reach of young children. This is most frequent in male toddlers,[ 1 2 3 4 5 ] and poverty, parental ignorance, and poor supervision fuel the childhood ingestion of poisons,[ 7 8 ] as was evident in all four cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 6 ] Economic hardship leads to overcrowded living with limited storage space for toxic substances away from the reach of young children. This is most frequent in male toddlers,[ 1 2 3 4 5 ] and poverty, parental ignorance, and poor supervision fuel the childhood ingestion of poisons,[ 7 8 ] as was evident in all four cases.…”
Section: Discussionmentioning
confidence: 99%
“…[ 1 ] Ingestion is the commonest route of poisoning, and commonly ingested substances include household items such as cosmetics, medication, detergents, and cooking fuel. [ 2 3 ] In low-income countries like Nigeria, the most common source of accidental poisoning which is responsible for up to 70% cases seen in pediatric emergency is a dangerous hydrocarbon known as kerosene (paraffin) commonly used as cooking fuel. [ 2 3 4 ] Kerosene ingestion is especially common during the hot, dry season, and risk factors include low socio-economic class, low parental education, poor supervision, overcrowded living situations, households with children under-five, male gender, and urban residence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, study reports from Kathmandu revealed that the same proportions of educated and uneducated patients were exposed to the ingestion of poison (2). Most of this study location reports were on intentional poisoning except for the University of Maiduguri Teaching Hospital (UMTH) report (22) and Federal Medical Centre (FMC) Azare reports (23) which were accidental. A study carried out in China among teenagers (adolescents) reveals that most cases were deliberate in females and males (27).…”
Section: Discussionmentioning
confidence: 99%
“…In a 5-year cross-sectional retrospective analysis carried out by Imoudu et al (23), from January 2013 to December 2017, acute poisoning amounted to 0.68% of the total admissions resulting in 684 per 100,000 prevalence rates. The ratio of females to males was 1:1.4 in the study.…”
Section: Case Study and Occurrence Datamentioning
confidence: 99%